ФОЛКЛОРИСТИЧКИТЕ ПОГЛЕДИ НА КОСТАНТИН МИЛАДНИНОВ (Filološke pripombe, 2019)
The collecting activity and consciousness about the national language are the foundations on which the platform for development of the nationally – cultural renascence is being built, not only in Macedonia, but all over Europe. This line is also followed by the work of Konstantin Miladinov in regard to collecting and publishing folklore materials. Undoubtedly, turning the public’s attention towards the national creatings had a significant influence in the process of creation of national consciousness. The subject of research of this paper is his contribution to the development of the folkloristics in Macedonia, reflected and realized in the “Collection”, through the classification of the collected poems and the foreword he wrote for this occasion.